2021
DOI: 10.1093/jamia/ocab029
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of prediction models for mechanical ventilation, renal replacement therapy, and readmission in COVID-19 patients

Abstract: Objective Coronavirus disease 2019 (COVID-19) patients are at risk for resource-intensive outcomes including mechanical ventilation (MV), renal replacement therapy (RRT), and readmission. Accurate outcome prognostication could facilitate hospital resource allocation. We develop and validate predictive models for each outcome using retrospective electronic health record data for COVID-19 patients treated between March 2 and May 6, 2020. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Logistic L1 had the best accuracy in the validation cohort. However, the discrimination results were inferior than the one observed in the present analysis (0.847 [95% CI, 0.772-0.936]) and the study has several limitations: many risk predictor variables, hindering the applicability of the score and high incidence of missing variables [29].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Logistic L1 had the best accuracy in the validation cohort. However, the discrimination results were inferior than the one observed in the present analysis (0.847 [95% CI, 0.772-0.936]) and the study has several limitations: many risk predictor variables, hindering the applicability of the score and high incidence of missing variables [29].…”
Section: Discussionmentioning
confidence: 65%
“…Using predictors available at baseline and within the first hours of the admission, we could objectively predict the probability of KRT of a COVID-19 patient with AKI. With an accurate prediction, it may help to organize resource allocation to patients who are at the highest risk of KRT requirement [29], in addition to selecting patients who may benefit from renal protection strategies, close assessment and follow-up by a nephrologist [31].…”
Section: Discussionmentioning
confidence: 99%
“…In Rodriguez's study (2021), a predictive model for readmission in COVID-19 patients was presented based on an ML classifier. They concluded that ML and data mining-based approaches have seemed fruitful for readmission prediction [ 20 ]. Koteswari (2020) proposed an intelligent model to predict the readmission probability of various COVID-19 cases using ML techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Since the COVID-19 pandemic began, several studies selected clinically important predictors for post-discharge COVID-19. For example, Rodriguez's study (2021) indicated underline chronic disease, hypoxia (oxygen saturation ≤94%), increased LDH, CRP, and ESR as the most effective factors on hospital readmission [ 20 ]. In another study performed by Mendito (2021), several clinical features such as age, neutrophilia count, sequential organ failure assessment (SOFA), LDH, CRP, and D-dimer are recognized as highly contributing factors to the readmission of COVID-19 patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation